2022
DOI: 10.29392/001c.35449
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to timely birth-dose vaccines in Kinshasa Province, the DRC: a qualitative study

Abstract: Background National vaccine policies across the world have successfully improved infant vaccine coverage, but birth-dose (BD) vaccine coverage remains low. Countries such as the Democratic Republic of the Congo (DRC) aim to include the hepatitis B birth-dose (HepB-BD) vaccine in their national immunization schedule. HepB-BD’s short window for administration – within 24 hours of delivery to prevent mother-to-child transmission – adds to the complexity of streamlined and timely BD vaccines. This study aims to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…Higher general readiness scores and attending a religiously a liated facility were independently associated with both BCG and HepB3 timely uptake, a nding that aligns with previous studies highlighting vaccine storage and stockout challenges in the DRC (13,21). In prior work, lower general facility readiness scores have been reported as barriers to timely immunization (22).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Higher general readiness scores and attending a religiously a liated facility were independently associated with both BCG and HepB3 timely uptake, a nding that aligns with previous studies highlighting vaccine storage and stockout challenges in the DRC (13,21). In prior work, lower general facility readiness scores have been reported as barriers to timely immunization (22).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast, visits to private, non-religious facilities were positively associated with timely uptake of both BCG and HepB3 than religious facilities. Previous studies on immunization uptake in SSA have cited a facility's religious a liation driving a mother's choice to seek care there (13). In terms of private facilities, studies show that mothers visiting private facilities tend to be of higher income levels (23), a factor that was positively associated with timely vaccine uptake and may explain our ndings.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Some respondents, mostly at regional or local levels, believed that training was missing, not frequent enough, or reached various levels of implementation at national to less local regions. Several studies have demonstrated the impact of training on delivery of immunization programs [15,28]. Some challenges to vaccination at the community level included language, geography, education or poverty status.…”
Section: Discussionmentioning
confidence: 99%